Route towards certification: a path analysis on licensure performance of new teacher education curriculum graduates - E. Senosa, Tedric Dave; Sagge, Jr., Roberto G. (Institute of Advanced Engineering and Science, 2025)
The board licensure examination for professional teachers (BLEPT) is a critical assessment for aspiring educators in the Philippines. Despite its vital importance, limited research has explored the comprehensive influence of the education graduates’ demographic background, psychological state, and achievement in the institutional parameters on the BLEPT performance. This study examined these influences on the licensure performance among 101 bachelor of secondary education (BSEd) mathematics and science graduates under the new teacher education curriculum. The researchers collected data using validated researcher-made questionnaires and educational metrics. Using structural equation modeling (SEM), results showed that the path model highlights the multifaceted nature of BLEPT performance, which shows that an intrinsic commitment towards the teaching profession and a supportive network create a cycle of positive experiences that fuels the graduates’ academic performance and self-efficacy, leading to a notable licensure performance. Likewise, the model emphasizes the vital effect of graduates’ education-related employment on their licensure examination performance. Taking these factors into account, teacher education institutions (TEIs) and key educational stakeholder should create targeted interventions, investigate unforeseen factors, and restructure curricula implementation to address the shortage of competent Filipino educators in these critical educational disciplines which are mathematics and science education.